Optimizing Parental Roles Through Parenting Programs to Foster the Development of Outstanding Children in Jadugan Hamlet - Hafif Komarullah; Yatik Wasilah; Betty Handayani; Humairoh Humairoh; Ismi Ulfatul Ilmiyah (Bale Pengabdian: Journal Of Community Service (BPJCS), 2026)
This community service program aimed to optimize parental roles through parenting activities in an effort to foster children with positive character in Dusun Jadugan. The main issue underlying this program was the limited understanding and involvement of parents in the child-rearing process, wherein children’s education was often perceived as the sole responsibility of schools. The program was implemented using a Participatory Action Research (PAR) approach that actively involved parents at every stage, including problem identification, action planning, implementation, and reflection. The participants consisted of 1s5 parents who took part in a parenting seminar based on dialogical interaction and shared experiences. The results indicated that the participatory PAR approach effectively encouraged active parental involvement and fostered new awareness of the importance of the family as the primary environment for children’s education and character development. The collective reflection process revealed a shift in parents’ perspectives toward more positive, communicative, and contextual parenting practices. The discussion of the program’s outcomes was further strengthened by relevant theoretical frameworks and previous studies on parenting, parental involvement, and community-based empowerment. Therefore, parenting programs based on the PAR approach proved to be relevant and effective as a community service model for optimizing parental roles and supporting children’s holistic and sustainable development.